Single Cell Mass Cytometry Revealed the Immunomodulatory Effect of Cisplatin Via Downregulation of Splenic CD44+, IL-17A+ MDSCs and Promotion of Circulating IFN-γ+ Myeloid Cells in the 4T1 Metastatic Breast Cancer Model - Balog, József Á. (Int J Mol Sci, 2019)
The treatment of metastatic breast cancer remained a challenge despite the recent breakthrough in the immunotherapy regimens. Here, we addressed the multidimensional immunophenotyping of 4T1 metastatic breast cancer by the state-of-the-art single cell mass cytometry (CyTOF). We determined the dose and time dependent cytotoxicity of cisplatin on 4T1 cells by the xCelligence real-time electronic sensing assay. Cisplatin treatment reduced tumor growth, number of lung metastasis, and the splenomegaly of 4T1 tumor bearing mice. We showed that cisplatin inhibited the tumor stroma formation, the polarization of carcinoma-associated fibroblasts by the diminished proteolytic activity of fibroblast activating protein. The CyTOF analysis revealed the emergence of CD11b+/Gr-1+/CD44+ or CD11b+/Gr-1+/IL-17A+ myeloid-derived suppressor cells (MDSCs) and the absence of B220+ or CD62L+ B-cells, the CD62L+/CD4+ and CD62L+/CD8+ T-cells in the spleen of advanced cancer. We could show the immunomodulatory effect of cisplatin via the suppression of splenic MDSCs and via the promotion of peripheral IFN-γ+ myeloid cells. Our data could support the use of low dose chemotherapy with cisplatin as an immunomodulatory agent for metastatic triple negative breast cancer.